Cache-less redundancy using hypergraph in information-centric network - Abdulllahi, Ibrahim; Che Mohamed Arif, Ahmad Suki; Hassan, Suhaidi (American Scientific Publishers, 2015)
Information dissemination has been the practice of today’s Internet with media data overtaking the ordinary textual information. A need to subscribe to Information-centric network has been seen as an option to provide better manageability of the future Internet. Caching is therefore assumed to be the most beneficial practice for fast delivery of information, saving cost and efficient bandwidth utilization. However, in the popular caching strategy, content and path redundancy has necessitated an extension for mitigating their effects. This paper provides an approach of mitigating high content and path redundancy in information-centric network using hypergraph properties of arcs and clustering. A comparison of some popular cache deployment strategies was analyzed based on simulation results. The paper proposes a cache deployment strategy using hypergraph with less content and path redundancy to improve content delivery in ICN.